Seed quality parameters of three interspecific hybrids of elephant grass x pearl millet - Pozitano,Marina (2012)
An interspecific hybrid resulting from the crossing of elephant grass (Pennisetum purpureum Schumach) x pearl millet (Pennisetum glaucum (L.) R. Brown) has been developed. This hybrid, however, revealed low phenotypic uniformity and low production of pure seeds. Through recurrent selection, two improved populations were obtained (genotypes Corte and Pastoreio). The aim of this study was assessing seed quality of the three hybrids (genotypes Corte, Pastoreio and Paraiso) by tests of: seed purity; seed germination; accelerated aging test, at 42 ºC; 1,000 seeds weight; drying curves; and sorption and desorption isotherms. Recurrent selection altered the seed size and increased initial quality of population for genotype Pastoreio. Drying curves for the three hybrids have shown similar behavior and reached moisture contents of 2.1%, 1.9%, and 1.8%, respectively, after 63 days. The accelerated aging test showed that hybrid Pastoreio was the most vigorous.